Reconstruction of Educator Responsibilities in Contemporary Education; Abd Al-Karim Bakkar's Perspective in The Digital Era - Fariq, Wan Muhammad; Salleh, Nor Hazrul Mohd (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
This study examines the responsibilities of educators in contemporary education from the perspective of Abd Al-Karim Bakkar amidst the digital era. This research seeks to answer two main questions: 1) What are the core responsibilities of educators according to Abd Al-Karim Bakkar's framework? and 2) How relevant are these responsibilities in addressing the challenges of the digital era? The method employed is a qualitative literature review (Library Research), utilizing content analysis to systematically identify and categorize themes within the text, combined with context analysis to understand the historical and intellectual environment of Bakkar's views on education. Primary data are sourced from Bakkar's book Ḥaul Al-Tarbiyyah Wa Al-Ta’līm, and secondary data are gathered from related journal articles, books, and other resources. The findings reveal that Abd Al-Karim Bakkar outlines seven responsibilities of educators, which include: (1) developing moral orientation; (2) educators as intergenerational connectors; (3) liberating the mind from its shackles; (4) facilitating students' goal-setting; (5) cultivating exploratory motivation and curiosity among students; (6) aligning teaching with students' cognitive development; and (7) curriculum and subject refinement. Additionally, the relevance of these responsibilities in the digital era encompasses the evolution of moral values, the educator's role in addressing the digital divide, fostering critical thinking, preparing youth for the workforce, and integrating digital skills into the curriculum to address future technological challenges. This study provides an overview of how educators' responsibilities must be reconstructed to align with the advancements of an era increasingly influenced by digital technology.